Additional of metal filler on graphite/carbon black/polypropylene composite as bipolar plate material for PEMFC application - Ahmad, Mohd Shakir (2015)
Polymer electrolyte membrane fuel cell (PEMFC) is expected to be one of the major power sources for future passenger vehicles since it features a high power density at a relatively low operating temperature of about 80◦C. There are several key components in PEMFC and one of them is bipolar plate. This bipolar plate is a multi-functional component. It provides the electrical connection from cell-to-cell and it separates the reactive gases. The known problem related to bipolar plate is the corrosion, weight and high cost. Hence, composite bipolar plate based on thermoplastic material is introduced and solved the general disadvantages of traditional bipolar plate. But, it still has a main limitation which is electrical conductivity and mechanical properties such as brittleness.. Through this research, the effect of secondary filler on electrical and mechanical properties is studied in order to overcome the main limitation of composite bipolar plate. The combination of metal and carbon filler also been studied for the purpose of improvement electrical and mechanical properties of G/PP composite bipolar plate. This study also would propose the fabrication process in producing composite material bipolar plate. The materials used in producing bipolar plate are greatly affecting its final properties. As for binder material, Polypropylene (PP) is used and for main filler material Graphite (Gr) is used. While, second filler used are Iron (Fe), Nickel (Ni) and Carbon Black (CB). The based ratio for this bipolar plate is 80%wt of filler and 20% wt of binder. The addition second filler is varying from 5%wt to 30%wt from the total of 80%wt. The fabrication of sample is done through compression molding method. The measurement that has been done is electrical conductivity, flexural strength, bulk density, shore hardness and microstructures. From result, the addition of CB has shown the most improvement in term of electrical conductivity (218.43 S/cm) and has good mechanical properties (38.03 MPa, flexural strength). While, the addition of Fe and Ni it not quite good but still Fe is better candidate than Ni. From this finding, another sample is introduced which is the combination of Fe and CB as part of second filler and it show the greater result which is 367.59 S/cm in electrical and 44.57 MPa in flexural strength. This result has shown a great improvement in electrical conductivity and acceptable mechanical properties. This framework of study can be used as reference in furthering the research.